CSR, Sustainability and Green IT in Higher Education: An Australian Perspective - Issa, Tomayess; Issa, Theodora (2017)
This research aims to examine and investigate the challenges and opportunities of promoting student's learning and awareness toward cooperative social responsibility (CSR) and Sustainability especially in higher education. General speaking, currently various sectors namely business, government, health, social and education started to adopt and integrate CSR and Sustainability in their strategies to enhance business reputation and make them unique in the market locally and globally. To promote and endorse CSR and Sustainability among postgraduate students, an Australian university developed a unit called ITS6 to enhance and improve students’ awareness of the roles information technology and information systems play in business, especially technology waste and recycling on the environment. The development of ITS6 unit derived after the Global Financial Crisis of 2007-2008 as business schools are amongst those who have been accused for economic, societal and environmental disappointments. ITS6 unit aims to raise students’ awareness of sustainability and Green IT and sustainability strategies proposed by recognized scholars within the field of strategy and sustainability (e.g. (Rainey 2006; Teece 2009). The empirical evidence from 85 students is based on quantitative and qualitative approaches; as data derived from formal and informal students’ feedback. The preliminary analyses of data collected revealed that the completing ITS6 especially the unit materials and assessments gave students a better understanding and knowledge in relation to new concepts and cutting edge CSR, Sustainability and Green IT. Furthermore, ITS6 assessments (i.e. reflective journals, wikis, digital presentation and report writing) managed to increase students awareness towards CSR, sustainability, and improve students’ personal and professional skills for the current study as well the workforce in future. In addition, students show their satisfaction with ITS6 assessments, as it develops specific skills for the current study and for the future workplace, i.e. cultural awareness and cutting edge.